The Determination of Maintenance Tasks Based on Reliability-Centered Maintenance Analysis on Equipments of Gas Distribution System - FAISYA (nim : 13113086), RAIHAN
Natural gas distribution activity for its widely utilization in Indonesia is supported by natural gas pipelines. Natural gas distribution process has to be guaranteed by performance monitoring activity for the pipelines to prevent failures or its failure effects does not cause major accidents. Reliability-Centered Maintenance (RCM) is a method to determine the suitable maintenance task for every equipment. RCM is performed based on the RCM seven basic questions and RCM decision diagram to determine failure consequences and suitable maintenance tasks for the equipment which would be written on RCM decision worksheet. Maintenance task for 966 equipment (5729 failure modes and effects) in 22 survey location had been determined by RCM. Equipment with low Equipment Criticality Rating (ECR) value, 78 of its failure modes and effects (2.38%) were assigned to preventive tasks, 3196 of its failure modes and effects (97.62%) were assigned to default tasks. Equipment with medium ECR value, 24 of its failure modes and effects (3.39%) were assigned to preventive tasks, 685 of its failure modes and effects (96.61%) were assigned to default tasks. Equipment with high ECR value, 475 of its failure modes and effects (39.09%) were assigned to preventive tasks, 740 of its failure modes and effects (60.91%) were assigned to default tasks. All of the equipment with extreme/vital ECR value (532 failure modes and effects) were assigned to preventive tasks.